The divergent effects of resilience qualities and resilience support in predicting pre-competition anxiety and championship performance - Zhang, S.; Wang, L.; He, Y.; Liu, J. D. (Research Quarterly for Exercise and Sport, 2024)
Purpose: Psychological resilience is vital to the development of sport talents. Qualitative research has consistently demonstrated that sport resilience encapsulates a mixed package of resilience qualities (reflecting positive traits and characteristics) and resilience support (reflecting perceived support and related resources). Ironically, sport resilience research adopting quantitative methods has been assessing resilience as a unidimensional construct, with little attention to the multi-facet nature of resilience and its effects on performance. In the present research, we tested a novel proposition that resilience qualities predict reduced pre-competition cognitive anxiety and contribute to performance more than resilience support.